(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the volatile compounds present in Tommy Atkins mango peel and kernel flour and in an ice cream cone made with this flour. In the preparation of the cone, 41% of the wheat flour of the traditional recipe was replaced by the flour of mango co-products. The volatile compounds were analyzed by solid phase microextraction in head space mode combined with gas chromatography and mass spectrometry. Twenty-nine volatile compounds were identified in flour produced with mango co-products, consisting mainly of terpenes (89.7%), of which 22 (75.9%) remained in the ice cream cone. The percentage distribution of the compounds in the ice cream cone was different from that of flour, with a decrease in the classes of aldehydes and sesquiterpenes and an increase in monoterpenes. It is concluded that of the 29 volatile compounds present in the flour prepared with mango co-products, most (n=22) remained in the ice cream cone, even using high temperatures in the production process, making the developed product present flavor and characteristic aroma of mango.